THE SELF ASSESSMENT CORNER ( SAC METHOD): A NOVEL WAY TO SELF ASSESS SHOULDER ROTATOR CUFF STRENGTH: A RELIABILITY AND VALIDITY STUDY. Issue 4 (1st February 2017) - Decleve, Philippe; Cools, Ann
Abstract : Background: Risk factors among overhead athletes have been investigated in many studies. The rotator cuff external rotator weakness is associated with an increased probability of substantial shoulder problems and throwing related injury requiring surgical intervention. Objective: To evaluate the relative and absolute reliability and the validity of the SAC method (SAC) that allows measurement of shoulder internal and external rotator isometric strength by the patient himself with the use of a hand-held dynamometer (HHD) fixed on a stabilization device. Design: A two session measurement design was used. Setting: laboratory setting. Patients (or Participants): 46 healthy adult participants (26 males and 20 females) aged between 18 and 25 years. Interventions (or Assessment of Risk Factors): Strength was measured using the SAC in a 0°0° and 90°90° shoulder position and compare to the HHD manual muscle testing in a standing (STAN) and sitting position (SIT). Main Outcome Measurements: Relative reliability was determined by intraclass correlation coefficients (ICC). Absolute reliability was quantified by standard error of measurement (SEM) and minimal detectable change (MDC). Systematic differences among similar measurements under different testing circumstances, were analyzed with Related Samples Wilcoxon Signed Rank Test or Kruskall Wallis Test. Results: Results showed relative reliability was good to excellent ranging from 0.85 (IR 0°0°) to 0.92(IR 90°90°). Absolute reliability showed MDC90% varying from 8.06 N (IR 90°90°) to 15, 69 N (IR 0°0°) and SEM varying from 3, 45 N (IR 90°90°) to 6, 72 N (IR 0°0°). Comparative analysis of similar measurements showed no statistically diferences between SAC and STAN in a 0°0° position as well as in a 90°90° position between SAC, STAN and SIT. Conclusions: We demonstrated a clinically applicable method, reliable and valid for self assessing rotator cuff isometric strength.